Lack of in vitro resistance of Candida albicans to ketoconazole, itraconazole and clotrimazole in women treated for recurrent vaginal candidiasis. Issue 1 (February 1993) - Fong, I W; Bannatyne, R M; Wong, P
Abstract : OBJECTIVE--To determine whether in vitro resistance of Candida albicans to the imidazoles (ketoconazole, clotrimazole and itraconazole) is associated with recurrence of candida vaginitis. DESIGN--Candida isolates were collected before, during and after treatment from women with recurrent vaginal candidiasis (> or = 4 episodes/year), randomised into two prospective studies: (1) 56 women treated with ketoconazole 400 mg/daily for 7 days; (2) 44 women randomised to receive itraconazole 200 mg orally, or clotrimazole 200 mg intravaginally, twice weekly for six months. SETTING--Women's Candida Clinic at St. Michael's Hospital, a University of Toronto teaching Hospital, Toronto, Ontario, Canada. MAIN OUTCOME, MEASURES--Isolates of yeasts recovered pre and post treatment were tested for significant changes in 50% inhibitory concentration (IC50). Resistance was defined as a greater than fourfold increase in baseline IC50 of post treatment isolates compared with pretreatment isolates. RESULTS--Over 250 strains of C albicans were tested and none showed development of resistance to any of the agents. CONCLUSION--Recurrence of vaginal candidiasis is not related to the development of drug resistance.